1987
DOI: 10.1128/aac.31.5.815
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of cefotaxime into respiratory secretions

Abstract: The objective of this study was to quantitate cefotaxime and its active metabolite, desacetyl cefotaxime, in the distal airways and to compare these levels to concentrations in plasma. Respiratory secretions were obtained from the subsegmental level in 17 adult patients undergoing fiber-optic bronchoscopy within 2 h after receiving four doses of cefotaxime (2 g intravenously every 6 h). In 11 patients, cefotaxime levels measured by high-pressure liquid chromatography in bronchial secretions were below detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Carece de actividad contra BGN no fermentadores (Pseudomonas aeruginosa, Acinetobacter baumannii), L. monocytogenes, Enterococcus spp y anaerobios estrictos. Dentro de sus características FC destacan: una mínima metabolización hepática cuyo metabolito activo es la des-acetil-cefotaxima, una amplia distribución en distintos fluidos corporales (logrando Antimicrobianos Documento concentraciones bactericidas en LCR y secreciones bronquiales), un aclaramiento renal variable (dependiendo del peso y EG) y una vida media en promedio de 3,6 h [14][15][16] . A pesar de todas las características mencionadas, su utilidad en neonatología es limitada, debido a que su uso en este tipo de pacientes se ha asociado con mayor mortalidad, como lo demostró el estudio realizado por Clark y cols., en el cual, los pacientes que recibieron la combinación ampicilina-cefotaxima versus ampicilina-gentamicina dentro de los primeros tres días de vida, tuvieron 1,5 más probabilidades de morir 17 .…”
Section: Cefotaximaunclassified
“…Carece de actividad contra BGN no fermentadores (Pseudomonas aeruginosa, Acinetobacter baumannii), L. monocytogenes, Enterococcus spp y anaerobios estrictos. Dentro de sus características FC destacan: una mínima metabolización hepática cuyo metabolito activo es la des-acetil-cefotaxima, una amplia distribución en distintos fluidos corporales (logrando Antimicrobianos Documento concentraciones bactericidas en LCR y secreciones bronquiales), un aclaramiento renal variable (dependiendo del peso y EG) y una vida media en promedio de 3,6 h [14][15][16] . A pesar de todas las características mencionadas, su utilidad en neonatología es limitada, debido a que su uso en este tipo de pacientes se ha asociado con mayor mortalidad, como lo demostró el estudio realizado por Clark y cols., en el cual, los pacientes que recibieron la combinación ampicilina-cefotaxima versus ampicilina-gentamicina dentro de los primeros tres días de vida, tuvieron 1,5 más probabilidades de morir 17 .…”
Section: Cefotaximaunclassified
“…A recent review by Todd and Brogden (1990) reported that desacetylcefotaxime penetrated into cerebrospinal fluid (CSF), sputum, bronchial secretions, bile, ascitic fluid and peritoneal fluid. There are also data suggesting that during treatment with cefotaxime, high concentrations of desacetylcefotaxime occur in sputum and bronchial secretions (Fick et al 1987;Matsuoka et al 1986;Petrikkos et al 1987). Whether this apparent accumulation occurs because of an innate physicochemical property of desacetylcefotaxime or differences in the pharmacokinetics of the parent drug and/or active metabolite remains to be determined.…”
Section: Antimicrobial Pharmacodynamicsmentioning
confidence: 99%
“…That is, the level in the airways will be only 20 to 30% of a simultaneously obtained serum concentration. 15,88 Additionally, Levy and coworkers 89 demonstrated biologic antagonism of gentamicin in CF purulent sputum caused by protein binding and antagonism by ions reducing antibiotic bioactivity. For these reasons, nebulized delivery has been more frequently resorted to in an attempt to attain suprapharmacologic levels of bactericidal antibiotics in these chronically infected airway fluids.…”
Section: Antimicrobial Penetrationmentioning
confidence: 99%